Analisis Pengaruh Experiential Marketing terhadap Kepuasan Pelanggan Pada E- Resto Semarang - Noviarini, Amanda Pramesty; Khasanah, Imroatul (Diponegoro Journal of Management, 2014)
This research is motivated by the increasing level of customer complaints and followed by a declining number of subscriber in a row at E - Resto Semarang . This research effort undertaken to review the E - Resto to improve overall customer satisfaction using experiential marketing elements and become flagship restaurant in Semarang . The effort by E-Resto so far to improve customer satisfaction are unconditional guarantee for its  food  and  drink  and  efficient  complain  handling  by  taking  their  guest  comment positively. This study examines the elements of experiential marketing which consists of sense , feel , think, act and relate that affect customer satisfactionThrough the questionnaire method using techniques purposive sampling to 100 respondents who ever came and mergkonsumsi E - Resto Semarang products showed the regression equation as follows :Y = 0.202 X1 + 0.187 X2 + 0.199 X3 + 0.203 X4 + 0.188 X5Where all the independent variables have a positive and significant impact on customer satisfaction.  Figures  Adjusted  R  Square  of  0.594  indicates  that  59.4  percent  of  the variation can be explained by the Customer Satisfaction to - five independent variables in the regression equation . While the remaining 40.6 percent is explained by other variables outside the five variables used in this study.